Interactive effect of elevated CO2 and drought on physiological traits of Datura stramonium - Javaid, Muhammad Mansoor; Florentine, Singarayer; Mahmood, Athar; Wasaya, Allah; Javed, Talha; Sattar, Abdul; Sarwar, Naeem; Kalaji, Hazem M.; Ahmad, Hafiz Bashir; Worbel, Jacek; Ahmed, Mohammed A. A.; Telesiński, Arkadiusz; et al. (Frontiers in Plant Science, 2022)
Rising atmospheric CO2 concentration is known to influence the response of many plants under drought This paper aimed to measure the leaf gas exchange, water use efficiency, carboxylation efficiency and photosystem II (PS II) activity of Datura stramonium, under progressive drought conditions alongwith ambient conditions of 400 ppm (aCO2) and elevated conditions of 700 ppm (eCO2). Plants of D. stramonium were grown at 400 ppm and 700 ppm under 100 and 60% field capacity in a laboratory growth chamber. For 10 days at two-day intervals, photosynthesis rate, stomatal conductance, transpiration rate, intercellular CO2 concentration, water use efficiency, intrinsic water use efficiency, instantaneous carboxylation efficiency, PSII activity, electron transport rate and photochemical quenching were measured. Whilst drought stress had generally negative effects on the aforementioned physiological traits of D. stramonium, it was found that eCO2 concentration mitigated the adverse effects of drought and most of the physiological parameters were sustained with increasing drought duration when compared to that with aCO2. Datura stramonium which was grown under drought conditions, was re-watered at day 8 and indicated a partial recovery in all the parameters except maximum fluorescence, this recovery being higher with eCO2 compared to aCO2. These results suggest that elevated CO2 mitigates the adverse growth effects of drought, thereby enhancing the adaptive mechanism of this weed by improving its water use efficiency. It is concluded that this weed has the potential to take advantage of climate change by increasing its competitiveness with other plants in drought-prone areas, suggesting that it could expand into new localities.